2021
DOI: 10.3390/ecologies2010010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Content and Mesh Size on Tea Bag Decomposition

Abstract: The tea bag method provides a replicable and standardized method to study the effect of environmental variables on the decomposition of standard litter, which enables comparison of organic matter decomposition rates on a large scale. However, it remains uncertain whether tea bag decomposition in response to wetness is representative of that of local litters. We performed incubation experiments to examine whether the effect of soil water on tea bag decomposition becomes inhibitory at higher water contents, as i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The bags were oven‐dried at 70°C for 72 h and the dry weight was determined. As the tea bag manufacturer Lipton changed the tea bag mesh from woven nylon 0.25 mm mesh to nonwoven polypropylene mesh (Teatime 4 Science, http://www.teatime4science.org/), we reproduced woven tea bags using 0.25 mm mesh (polyester) and tea inside the nonwoven tea bags following Mori, Aoyagi, et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…The bags were oven‐dried at 70°C for 72 h and the dry weight was determined. As the tea bag manufacturer Lipton changed the tea bag mesh from woven nylon 0.25 mm mesh to nonwoven polypropylene mesh (Teatime 4 Science, http://www.teatime4science.org/), we reproduced woven tea bags using 0.25 mm mesh (polyester) and tea inside the nonwoven tea bags following Mori, Aoyagi, et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Surface soils (0–10 cm) were sampled from four randomly selected subplots established in a Japanese cedar [ Cryptomeria japonica (L.f.) D.Don] plantation located at the Tatsudayama research site in Kumamoto, Japan (32.82 N, 130.73 E). Previous studies reported that the mean annual temperature and precipitation amounts at the research sites were 17.1°C and 1951 mm, respectively (Mori et al, 2021a) (data obtained from the Agro-Meteorological Grid Square Data of the National Agriculture and Food Research Organization). Sampled soils were sieved through a 4-mm sieve after the removal of large pieces of organic matter.…”
Section: Methodsmentioning
confidence: 99%
“…A pair of tea bags (green and rooibos) was buried in 100 g of freshly sampled soil placed in a plastic (polyethylene terephthalate) bottle. The soil moisture was adjusted to 45% (w/w) because a previous study at the same site demonstrated that tea decomposition rates were highest around this moisture level (Mori et al, 2021a). Twenty bottles (4 subplots × 5 time-series) were placed in a cold room (3°C) for 5, 13, 23, 58, and 90 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could mask the contribution of other decomposition drivers at the local scale, such as variations in the microbial communities (Bradford et al, 2017). In addition, because water availability is an important driver of mass loss in tea bags (Djukic et al, 2018;Blume-Werry et al, 2021;Mori et al, 2021), the local-scale conditions of soil moisture measured continuously throughout the incubation period may better explain the variation in initial decomposition rates.…”
Section: Organic Matter Inputmentioning
confidence: 99%